Labour migration in Europe and the New Economic Geography - Mark Thissen; Frank Van Oort (European Regional Science Association (ERSA), 2004)
This paper addresses consequences of increased labour migration in Europe due to productivity effects in a core-periphery model. Traditional trade and growth models predict an overall beneficial impact of the accession of the current candidate states to the European Union. However, models incorporating imperfect competition warn that peripheral countries may realise only a small portion of this beneficial impact of the accession. In this chapter we go a step further: On the domestic level the countries accession may have negative effects while on the nationals level the effect will be positive. An empirical indication that benefits of accession may be low is the marginal benefits during the early phases of EU membership for Greece and Ireland and the Neue Länder of Germany. The following main questions are addressed in this chapter. What is the consequence of increased migration within the European Union due to deregulation in the context of the creation of a common market, and what will be the consequence of the extension of the European union with central and eastern European countries?
Keywords: 330